HARMONI LINTAS AGAMA DI MEDIA MASSA - Mohammad Ali Hisyam (Program Studi Ilmu Agama Islam Program Magister, Universitas Islam Indonesia, 2009)
The article is intended to elaborate the problems of dialogue among religions in mass media discourse that is occurred in Indonesia within last few years. At the end, it tries to offer alternative solutions that may be suitable with the problem. The analysis indicates that mass media has a strategic role to support the dialogue. However, the role should be followed by the awareness of the mass media to be consistent and commited to maintaining the harmony among religions. The mass media should not change its objective.